Jogo de xadrez como unidade didática interdisciplinar : uma proposta pedagógica segundo a visão do professor de educação física - Ferreira, Widson Marçal (2023)
This paper describes the development of a pedagogical proposal which, by arousing the interest of elementary school students in studying the game of chess in Physical Education classes, promoted interdisciplinarity with the curricular components of Art, Mathematics, Geography and History. The pedagogical experiences demonstrated the importance of teaching and learning chess as an interdisciplinary tool that contributes to autonomy, collectivity and the improvement of psychological, social and affective skills among students in a playful way. The general objective is to present a didactic unit focused on the concept of interdisciplinarity based on the game of chess, contextualizing it with different disciplines. The specific objectives were: To describe an interdisciplinary pedagogical proposal, using the game of chess as the object of this study. To develop a didactic unit that explores the teaching of the game of chess in Physical Education classes, in an interdisciplinary and playful way, promoting integration with other disciplines.The research has a qualitative approach. Two open-ended questionnaires were used as data collection instruments. The first was an entry diagnosis and the second was applied at the end of the intervention to evaluate the pedagogical process. The students/participants answered the questionnaires in person, in the school environment. Another data collection tool used in this study was the field diary, in which participant observations were recorded, taking notes of events that occurred during the process of implementing the didactic unit. The contribution of this work lies in how the use of chess as an interdisciplinary integration enriched students' education by developing cognitive skills, promoting interdisciplinarity, improving social and emotional skills, stimulating autonomy, contextualizing learning, fostering creativity and preparing students for the challenges of the 21st century. This approach not only promoted a more complete and meaningful education, but also demonstrated the potential of chess as a valuable educational tool that broadened horizons and strengthened essential skills.